Emphasizing Greenhouse Gas Emissions: “Potemkin Villages” and Global Resilience - Lane, Jan-Erik (New Horizons in Education and Social Studies Vol. 9, 2021)
The climate change problematic, becoming more relevant every day, is almost exclusively approached as a natural sciences concern. Thus, scholars debate what drives global warming physically as well as whether a fundamental turn to renewable energy would mean much difference. As global warming intensifies and its link to man-made emissions becomes ever more evident, one may take a look at how different countries differ in terms of the evolution of emissions during the last two decades. The point in this paper is that what the social sciences have to say about the possibility and desirability of a global policy must NOT be pushed aside. Of course, the chemical and biological processes inherent in global warming should be identified and measured in an ever more detailed manner, but policy-making is conducted by human beings in social, economic and political settings. Only the governments of the world can engage in global coordination to halt global warming, but the lessons from political theory underlining opportunism as well as self-seeking with guile and moreover game theory with asymmetric information teach humbleness and scepticism about these prospects. The states coordination coin has two sides: talk, meetings, declarations, promises on the one side, and reneging, cheating and opportunism with guile on the other less shining side.